Groundwater Sustainability and Solar Irrigation in Madhesh Province: Status, Challenges, and Integrated Solutions - Karki, Sajina (International Research Journal of Parroha, 2025)
In pursuit of sustainable agriculture, Madhesh Province is witnessing a rapid transition from diesel and electric pumps to solar-powered irrigation systems. While this shift reduces carbon emissions and energy costs, it raises critical concerns regarding groundwater sustainability. Currently, groundwater levels in the region are not systematically monitored, and the natural recharge rates of extracted water remain uncertain. Without concurrent investments in groundwater recharge infrastructure, restoration of the Chure–Bhabar ecological zone, and regulation of tubewell installation, the widespread adoption of solar irrigation risks exacerbating groundwater depletion. This paper critically reviews the current status of groundwater resources in Madhesh Province alongside the rapid diffusion of solar irrigation technologies. It highlights the gap between renewable energy adoption and sustainable water resource management, underscoring potential long-term risks of unsustainable abstraction. Building on this analysis, the paper proposes integrated, multi-dimensional solutions: combining solar irrigation with strategically designed recharge ponds, reinforcing aquifer recharge through ecological restoration of Chure–Bhabar, and implementing regulatory frameworks for tubewell installation. Furthermore, it explores opportunities for multi-purpose solar utilization to optimize resource use. By synthesizing hydrological data and technology trends, this study emphasizes the necessity of coupling solar-powered irrigation with effective groundwater management to ensure the resilience of Madhesh’s water and agricultural systems.